2010
DOI: 10.1021/bi1016815
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Formation of a Transient Tryptophan Synthase Complex with αββ Subunit Stoichiometry

Abstract: The prototypical tryptophan synthases form a stable heterotetrameric αββα complex in which the constituting TrpA and TrpB1 subunits activate each other in a bidirectional manner. The hyperthermophilic archaeon Sulfolobus solfataricus does not contain a TrpB1 protein but instead two members of the phylogenetically distinct family of TrpB2 proteins, which are encoded within (sTrpB2i) and outside (sTrpB2a) the tryptophan operon. It has previously been shown that sTrpB2a does not functionally or structurally inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…1 It has been shown that the ssTrpB2i enzyme from Sulfolobus solfataricus forms with ssTrpA a transient, ligand-dependent tryptophan synthase complex having αββ stoichiometry. 8,9 This finding indicates a functional equivalence of TrpB2i and TrpB1 in vivo. In contrast, all TrpB2o and TrpB2a enzymes characterized to date do not interact with TrpA.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…1 It has been shown that the ssTrpB2i enzyme from Sulfolobus solfataricus forms with ssTrpA a transient, ligand-dependent tryptophan synthase complex having αββ stoichiometry. 8,9 This finding indicates a functional equivalence of TrpB2i and TrpB1 in vivo. In contrast, all TrpB2o and TrpB2a enzymes characterized to date do not interact with TrpA.…”
mentioning
confidence: 64%
“…30 It has been shown that saturating concentrations of the ssTrpA ligand glycerol-3-phosphate (GP) and the ssTrpB2i ligand L-serine induce the formation of a transient αββ complex. 8 We tested the consequences of replacing L-serine by O-phospho-L-serine or glycine for complex formation between ssTrpB2i and ssTrpA. Surface plasmon resonance and isothermal titration calorimetry showed that the affinity between ssTrpB2i and ssTrpA was identical, independent of the used ssTrpB2i ligand (Table S3, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The polysaccharide used in the current study is different from the previous reports in that it is also slowly utilized to some degree through the E. coli maltose-maltodextrin transport system (own unpublished results). The EnBase fed-batch-like medium has been successfully used for high-yield cytoplasmic expression of several non-disulfide bond containing proteins [22-27] as well as functional protein with multiple disulfide bonds [28,29], while in this study we apply this medium for the first time for periplasmic production of disulfide-containing proteins. We also compared two metabolically different E. coli strains regarding their Fab yield in the different growth media.…”
Section: Introductionmentioning
confidence: 99%
“…Among the TrpB2 proteins, only TrpB2o from T. maritima and TrpB2i from S. solfataricus (ssoTrpB2i) have been examined experimentally. It was found that ssoTrpB2i forms a weak and transient complex with TrpA from S. solfataricus (ssoTrpA) only in the presence of the substrate l ‐serine, and activates ssoTrpA unidirectionally . T. kodakarensis harbors a trpB1 gene within the trp operon and a trpB2 gene (tkTrpB2o) outside of the operon.…”
Section: Discussionmentioning
confidence: 99%